2021
DOI: 10.3390/ijms22179426
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Force—Induced 3D Chromosomal Conformational Changes Are Associated with Rapid Transcriptional Response in Human T Cells

Abstract: The mechanisms underlying gravity perception in mammalian cells are unknown. We have recently discovered that the transcriptome of cells in the immune system, which is the most affected system during a spaceflight, responds rapidly and broadly to altered gravity. To pinpoint potential underlying mechanisms, we compared gene expression and three-dimensional (3D) chromosomal conformational changes in human Jurkat T cells during the short-term gravitational changes in parabolic flight and suborbital ballistic roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 144 publications
8
23
1
6
Order By: Relevance
“…However, it should be pointed out, that during the parabolic flight, the Jurkat T cells were exposed to 31 alternating hypergravity, microgravity, and hypergravity phases, each lasting 20–22 sec ( Acharya et al., 2019 ). In striking contrast, in the present study, CMs were continuously exposed exclusively to microgravity for 48 h. Therefore, due to fundamental experimental differences of the Hi-C data in our study and the study reported ( Vahlensieck et al., 2021 ) are not surprising. Nevertheless, it is evident that SMG also impacts large-scale chromosomal organization.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…However, it should be pointed out, that during the parabolic flight, the Jurkat T cells were exposed to 31 alternating hypergravity, microgravity, and hypergravity phases, each lasting 20–22 sec ( Acharya et al., 2019 ). In striking contrast, in the present study, CMs were continuously exposed exclusively to microgravity for 48 h. Therefore, due to fundamental experimental differences of the Hi-C data in our study and the study reported ( Vahlensieck et al., 2021 ) are not surprising. Nevertheless, it is evident that SMG also impacts large-scale chromosomal organization.…”
Section: Discussioncontrasting
confidence: 86%
“…More recently, human Jurkat T cells were exposed to short-term gravitational changes in parabolic flight and suborbital ballistic rocket flight experiments ( Vahlensieck et al., 2021 ). Authors reported that smaller chromosomes (Chr 16–22 except for chr18) have higher intrachromosomal interactions compared to large chromosomes in altered gravity.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial organization of the genome is essential for modulating gene regulation ( Kong and Zhang, 2019 ). In mammalian T cells, there is a non-random overlap between regions of chromosome structural changes and regions of DEGs in response to gravity changes ( Vahlensieck et al, 2021 ). In addition, our previous study found that under SMG, most DEGs of Vibrio natriegens were located in regions with changeable chromosome structures ( Yin et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A/B compartment analysis also revealed that chromosomes became more active. For eukaryotes, Vahlensieck et al (2021) reported that under normal gravity the nucleus is compressed by the force of gravity along the vertical axis, thus shortening it along the vertical axis and elongating it along the horizontal axis. In microgravity, these forces are no longer present, and the shape of the nucleus becomes more circular ( Vahlensieck et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation